Mechanical Design and Dynamcis of an Autonomous Climbing Robot for Elliptic Half-shell Cleaning - Houxiang Zhang; Jianwei Zhang; Rong Liu; Guanghua Zong (International Journal of Advanced Robotic Systems, 2007)
This paper presents an auto-climbing robot for cleaning the elliptic half-shell of National Grand Theatre in China. The robot consists of a climbing mechanism, a moving mechanism, two cleaning brushes and supporting mechanisms. The mechanism and unique aspects are presented in detail. A distributed control system based on CAN bus is designed to meet the requirements of controlling the robot. After that the emphasis for discussion is on the motion realization which includes climbing and cleaning movements. The robot independently climbs and descends in the vertical direction and cleans in the horizontal direction. It takes the circling tracks as supports for climbing up and down between strips and moving horizontally along one strip around the ellipsoid. For system design and control purposes, the dynamic models of the climbing and cleaning processes are given applying of the Lagrange equation. Furthermore the force distribution of the front and rear supporting mechanisms is computed in a way that ensures the safety of the climbing process. In the end, the successful on-site tests confirm the principles described above and the robot's ability.